Hubungan Intensitas Nyeri Kepala Tipe Tegang Dengan Derajat Depresi - Padad, Andi Tenri; Muharram, Andi Fatmawati; Nyambe, Hasan (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2022)
Depression is a natural feeling disorder (mood) which is characterized by excessive feelings of sadness, depression, lack of enthusiasm, feeling worthless, feeling that life is empty and hopeless, thinking is centered on failure and self-blame or self-blame, and often accompanied by envy and suicidal thoughts. Depressive disorders can occur in anyone with a higher risk of physical illness, which is about 15-60%. Medical conditions that have long been associated with depressive disorders include primary tension-type headache (TTH). Patients with chronic TTH will experience more severe depression than episodic TTH and chronic headache is significantly associated with psychopathological scores, but the direction of the relationship is not clear. This study aims to determine the relationship between the intensity of tension-type headaches and the degree of depression. This research is an observational analytic study with a cross sectional research design. To find out the frequency and duration of tension-type headaches, the history and filling of the questionnaire provided were carried out. Then the Beck Depression Inventory (BDI) questionnaire was used to assess the degree of depression. Patients with tension headaches were assessed based on The International Headache Classification 2nd Edition in 2004, and pain intensity was assessed based on the NPRS (Numeric Pain Rating Scale) score. The results showed that the Spearman correlation test obtained a significance value of 0.014, a correlation value of 0.399. between the Numeric Pain Rating Scale (NPRS) and Visual Analog Scale (VAS) scores with the Beck Depression Inventory (BDI) score on the subject of tension-type headache, and there is a significant relationship between the intensity of the tension-type headache and depression where the higher the pain intensity, the more severe the pain. degree of depression.